Y-chromosome diversity suggests southern origin and Paleolithic backwave migration of Austro-Asiatic speakers from eastern Asia to the Indian subcontinent - Xiaoming Zhang (2018)
Analyses of an Asian-specific Y-chromosome lineage (O2a1-M95)-the dominant paternal lineage in Austro-Asiatic (AA) speaking populations, who are found on both sides of the Bay of Bengal-led to two competing hypothesis of this group's geographic origin and migratory routes. One hypothesis posits the origin of the AA speakers in India and an eastward dispersal to Southeast Asia, while the other places an origin in Southeast Asia with westward dispersal to India. Here, we collected samples of AA-speaking populations from mainland Southeast Asia (MSEA) and southern China, and genotyped 16 Y-STRs of 343 males who belong to the O2a1-M95 lineage. Combining our samples with previous data, we analyzed both the Y-chromosome and mtDNA diversities. We generated a comprehensive picture of the O2a1-M95 lineage in Asia. We demonstrated that the O2a1-M95 lineage originated in the southern East Asia among the Daic-speaking populations ~20-40 thousand years ago and then dispersed southward to Southeast Asia after the Last Glacial Maximum before moving westward to the Indian subcontinent. This migration resulted in the current distribution of this Y-chromosome lineage in the AA-speaking populations. Further analysis of mtDNA diversity showed a different pattern, supporting a previously proposed sex-biased admixture of the AA-speaking populations in India.